Early-onset cardiac dysfunction following allogeneic haematopoietic stem cell transplantation. Issue 1 (20th May 2022) - Moriyama, Shohei; Fukata, Mitsuhiro; Hieda, Michinari; Yokoyama, Taku; Yoshimoto, Goichi; Kusaba, Hitoshi; Nakashima, Yasuhiro; Miyamoto, Toshihiro; Maruyama, Toru; Akashi, Koichi
Abstract : Objective: Heart failure following allogeneic haematopoietic stem cell transplantation (allo-HSCT) is a serious complication that requires early detection; however, the clinical implications of early-onset cancer therapy-related cardiac dysfunction (CTRCD) following allo-HSCT remain unclear. We investigated the determinants and prognostic impact of early-onset CTRCD in allo-HSCT recipients. Methods: The records of 136 patients with haematological malignancies who underwent allo-HSCT at our institute were retrospectively reviewed. Early-onset CTRCD was defined as a decrease in left ventricular ejection fraction (LVEF) of ≥10% and an LVEF of ≤53% within 100 days after HSCT. Results: Early-onset CTRCD was diagnosed in 23 out of 136 included patients (17%), and the median duration from HSCT to CTRCD diagnosis was 24 (9–35) days. Patients were followed up for 347 (132–1268) days. In multivariate logistic regression analysis, cumulative doxorubicin dosage (each 10 mg/m 2 ) and severity of acute graft-versus-host disease (GVHD/grade) were independent indicators of early-onset CTRCD (OR (95% CI) 1.04 (1.00 to 1.07); p=0.032; OR (95% CI) 1.87 (1.19 to 2.95), p=0.004, respectively). The overall and primary disease death rates were significantly higher in allo-HSCT recipients with early-onset CTRCD than in those without early-onset CTRCD (HR (95% CI) 1.98 (1.11 to 3.52), p=0.016; HR (95% CI) 2.96 (1.40 to 6.29), p=0.005, respectively), independent of primary disease type, remission status and transplantation type. Conclusions: Severe acute GVHD and higher cumulative anthracycline are two significant determinants of early-onset CTRCD. Early-onset CTRCD following allo-HSCT regulates survival in patients with haematological malignancies.